Tuntutan Ganti Rugi dalam Perkawinan Singkat: Studi Putusan Mahkamah Rendah Syariah, Bera, Negeri Pahang, Kes Mal, No. 06013-049- 0159 Tahun 2020 dalam Perspektif Keadilan Hukum - Nurul Anis Izatul; Irwan Irwan (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
This article’s purpose is to provide information about Claims for Compensation in Short Marriages in the Decisions of the Lower Shariah Court, Bera, Pahang State, Kes Mal, No. 06013-049-0159 year 2020 Prospective on Legal Justice.Rejected the plaintiff's claim to seek compensation for the expenditure of wedding party expenses amounting to 30,000 Malaysian Ringgit in the content of the Syari'ah Lower Court Judgment in this article.The judge reasoned that there was no debt agreement between the plaintiff and the defendant in writing as valid evidence of the transaction.This research is a normative research by using a conceptual conceptual approach, namely by studying and looking for legal concepts or legal principles that are relevant to the case.The results of the research reveal that there is still room for the judge to accept some of the plaintiff's claims because de facto there has been a material and non-material loss suffered by the woman.